Fleshy Encounters: Meddling in the Lifeworlds of Zoo and Aquarium Veterinarians - Braverman, Irus (Humanimalia, 2020)
This article aims to make visible expert practices that take place behind closed doors and that are perceived as being of no concern to the public, who wouldn’t understand them anyway. The experts that this article is concerned with are medical practitioners of a particular kind: zoo and aquarium veterinarians. I utilize both text and multimedia presentations to allow the veterinarians I interviewed to directly explain their work to the reader, who may then experience this work, the space and environment where it is performed, and the tools with which it is conducted, on a more affective and sensorial plane. Quotes from the scholarly literature and from the interviews are intended to provide context and set the tone for the visual and auditory experiences, which are an inherent and important part of the article. My hope is that readers emerge from this inquiry knowing more about how veterinarians see, think, and operate in their professional encounters. The idea, more broadly, is that we ought to immerse ourselves, mess with, and meddle in each other’s professional lifeworlds in order to enrich and broaden our understandings of our currently much too self-, siloed-, and human-centric place on this planet.